2021
DOI: 10.3390/pharmaceutics13081232
|View full text |Cite
|
Sign up to set email alerts
|

A Tri-Stimuli Responsive (Maghemite/PLGA)/Chitosan Nanostructure with Promising Applications in Lung Cancer

Abstract: A (core/shell)/shell nanostructure (production performance ≈ 50%, mean diameter ≈ 330 nm) was built using maghemite, PLGA, and chitosan. An extensive characterization proved the complete inclusion of the maghemite nuclei into the PLGA matrix (by nanoprecipitation solvent evaporation) and the disposition of the chitosan shell onto the nanocomposite (by coacervation). Short-term stability and the adequate magnetism of the nanocomposites were demonstrated by size and electrokinetic determinations, and by defining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 137 publications
(177 reference statements)
0
10
0
Order By: Relevance
“…Therefore, CS-coated PLGA nanosystems can increase biocompatibility, protect from opsonization and improve retention and cellular uptake [ 98 , 99 ]. Additionally, CS coating has been used as a strategy to achieve sustained and pH-responsive drug release from PLGA nanostructures [ 100 , 101 , 102 ].…”
Section: Surface Modification Strategiesmentioning
confidence: 99%
“…Therefore, CS-coated PLGA nanosystems can increase biocompatibility, protect from opsonization and improve retention and cellular uptake [ 98 , 99 ]. Additionally, CS coating has been used as a strategy to achieve sustained and pH-responsive drug release from PLGA nanostructures [ 100 , 101 , 102 ].…”
Section: Surface Modification Strategiesmentioning
confidence: 99%
“…Furthermore, it can be used in treatment of infectious diseases such as COVID‐19 that is inflicting nowadays. 55 , 56 , 57 , 58 , 59 , 60 The CS‐based nanostructures have demonstrated great efficacy in prolonged delivery of drugs 61 , 62 that is of utmost importance in cancer therapy. Due to CS's positive charge, it can easily form complexes with negatively charged nucleic acids.…”
Section: Chitosan: Chemistry and Biomedical Applicationmentioning
confidence: 99%
“…Notably, CS‐based nano‐scale delivery systems for pulmonary delivery are of importance in treatment of related cancers such as lung tumor. Furthermore, it can be used in treatment of infectious diseases such as COVID‐19 that is inflicting nowadays 55–60 . The CS‐based nanostructures have demonstrated great efficacy in prolonged delivery of drugs 61,62 that is of utmost importance in cancer therapy.…”
Section: Chitosan: Chemistry and Biomedical Applicationmentioning
confidence: 99%
“…16 Thus, the synthesis procedures following the co-precipitation route are typically described in research studies with small volumes of up to 1 L and a small amount of product. 11,[17][18][19][20] The largest reported co-precipitation process syntheses are in the range up to 1.2 L total volume and 5.4 g L −1 of product. 21,22 To our knowledge, no study has reported a transfer from the laboratory to larger scales and the challenges associated with the scale-up yet.…”
Section: Introductionmentioning
confidence: 99%
“…16 Thus, the synthesis procedures following the co-precipitation route are typically described in research studies with small volumes of up to 1 L and a small amount of product. 11,17–20 The largest reported co-precipitation process syntheses are in the range up to 1.2 L total volume and 5.4 g L −1 of product. 21,22…”
Section: Introductionmentioning
confidence: 99%